Prospective study for the early detection of lung carcinoma in patients with HIV infection (GESIDA study 8815) - Valencia, M. Eulalia; Pirogova, Tatiana; Romera, Delia; Montero, Marta; Tasías, María; Sanz, José; Arranz, Alberto; Vergas, Jorge; Tellez, M. Jesús; Fanjul, Francisco; Campins, Antoni; Cervero, Miguel; et al. (Elsevier, 2025)
Introduction Lung cancer (LC) screening detects tumors early. The prospective GESIDA 8815 study was designed to assess the usefulness of this strategy in HIV + people (PLHIV) by performing a low-radiation computed tomography (CT) scan. Patients and methods 371 heavy smokers patients were included (>20 packs/year), >45 years old and with a CD4+ <200 mm3 nadir. One visit and CT scan were performed at baseline and 4 for follow-up time annually. Results 329 patients underwent the baseline visit and CT (CT0) and 206 completed the study (CT1 = 285; CT2 = 259; CT3 = 232; CT4 = 206). All were receiving ART. A total >8 mm lung nodules were detected, and 9 early-stage PCs were diagnosed (4 on CT1, 2 on CT2, 1 on CT3 and 2 on CT4). There were no differences between those who developed LC and those who did not in sex, age, CD4+ nadir, previous lung disease, family history, or amount of packets/year. At each visit, other pathologies were diagnosed, mainly COPD, calcified coronary artery and residual tuberculosis lesions. At the end of the study, 38 patients quit smoking and 75 reduced their consumption. Two patients died from LC and 16 from other causes (p = 0.025). Conclusions The design of the present study did not allow us to define the real usefulness of the strategy. Adherence to the test progressively decreased over time. The diagnosis of other thoracic pathologies is very frequent. Including smokers in an early diagnosis protocol for LC could help to quit smoking.